2017
DOI: 10.1016/j.tvjl.2017.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Cats with diabetes mellitus have diastolic dysfunction in the absence of structural heart disease

Abstract: Diabetes mellitus (DM) can result in cardiovascular dysfunction and heart failure characterized by diastolic dysfunction with or without the presence of systolic dysfunction in people and laboratory animals. The objective of this prospective study was to determine if cats with newly diagnosed DM had myocardial dysfunction and, if present, whether it would progress if appropriate antidiabetic therapy was commenced. Thirty-two diabetic cats were enrolled and received baseline echocardiographic examination; of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…Existence of a comparable cardiomyopathy related to hyperinsulinemia in cats remains controversial. Although diastolic dysfunction and increased risk of heart failure have been observed in diabetic cats, maximum left ventricular wall thickness was not significantly different in a study comparing diabetic and healthy cats . The effects of insulin and IGF‐1 are strongly related, because insulin and IGF‐1 fully activate their own receptors, and also, although with decreased affinity, bind and activate the other receptor .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Existence of a comparable cardiomyopathy related to hyperinsulinemia in cats remains controversial. Although diastolic dysfunction and increased risk of heart failure have been observed in diabetic cats, maximum left ventricular wall thickness was not significantly different in a study comparing diabetic and healthy cats . The effects of insulin and IGF‐1 are strongly related, because insulin and IGF‐1 fully activate their own receptors, and also, although with decreased affinity, bind and activate the other receptor .…”
Section: Discussionmentioning
confidence: 94%
“…Existence of a comparable cardiomyopathy related to hyperinsulinemia in cats remains controversial. Although diastolic dysfunction29 and increased risk of T A B L E 4 Significant associations between variables from different parts of the hypothesized mechanism 0.29, P = .04) IGF-1 (r = 0.44, P = .001) BCS Insulin (ρ = 0.33, P = .02) Glucose (ρ =0.29, P = .04) IGF-1 (ρ = 0.32, P = .02) IVSd Max-IVSd (ρ = 0.32, P = .05) n-IVSd (ρ = 0.28, P = .05) LVWd Max-LVWd (ρ = 0.41, P = .01) LA LA/Ao (ρ = 0.52, P = .001) LAmax (ρ = 0.32, P = .05) LA remodeling (ρ = 0.38, P = .02) LA/Ao (ρ = 0.49, P = .001) LAmax (ρ = 0.28, P = .05) LA remodeling (ρ = 0.38, P = .01) Abbreviations: BCS, body condition score; BW, body weight; cTnI, cardiac troponin-I; IGF-1, insulin-like growth factor-1; LA/Ao, left atrium to aorta ratio; LA-max, maximum diameter of left atrium; Max-IVSd, maximum thickness of interventricular septum in diastole; Max-LVWd, maximum thickness of left ventricular free wall in diastole; n-IVSd, number of regions in interventricular septum in diastole ≥6 mm; n-LVWd, number of regions of left ventricular free wall in diastole ≥6 mm; SAA, serum amyloid A.…”
mentioning
confidence: 99%
“…Although diabetes causes LV hypertrophy in humans [ 41 , 42 ], the cardiovascular effect of diabetes in cats is poorly understood. One retrospective case series did report a greater prevalence of cardiac disease in diabetic cats than age-matched controls [ 43 ], whilst another study evaluating serial echocardiographic changes in cats with DM suggested that diastolic dysfunction was associated with the diabetic state [ 44 ]. No studies investigating the potential pro-hypertrophic effect of DM in cats have been published.…”
Section: Introductionmentioning
confidence: 99%
“…Another study sought to assess cardiac function in feline patients with newly diagnosed DM and to characterise any development over the course of 6 months. 11 This showed that cats with DM had evidence of diastolic, but not systolic, dysfunction, in the absence of structural heart disease and when compared with healthy controls. This study excluded cats with primary heart disease as far as possible, including those with evidence of HCM on echocardiography; however, there was no histopathological assessment of these cases.…”
Section: Introductionmentioning
confidence: 97%